A dynamic data structure for flexible molecular maintenance and informatics - Bajaj, Chandrajit; Chowdhury, Rezaul Alam; Rasheed, Muhibur (Bioinformatics, 2011)
Motivation: We present the 'Dynamic Packing Grid' (DPG), a neighborhood data structure for maintaining and manipulating flexible molecules and assemblies, for efficient computation of binding affinities in drug design or in molecular dynamics calculations. Results: DPG can efficiently maintain the molecular surface using only linear space and supports quasi-constant time insertion, deletion and movement (i.e. updates) of atoms or groups of atoms. DPG also supports constant time neighborhood queries from arbitrary points. Our results for maintenance of molecular surface and polarization energy computations using DPG exhibit marked improvement in time and space requirements. Availability: http://www.cs.utexas.edu/~bajaj/cvc/software/DPG.shtml Contact: bajaj@cs.utexas.edu Supplementary information: Supplementary data are available at Bioinformatics online.